Differentiated surgical treatment of cervical discs herniations (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The variety of clinical manifestations and pathophysiological forms of development of compression syndromes at the level of the cervical spine with stenosis of the spinal canal of the cervical localization necessitates differentiated approaches to surgical treatment